Perception of American English allophonic variant /ɾ/ by Arabic speakers in an EFL context - Mustafa, Areej (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study investigates Saudi university students' perception of the allophonic variant /ɾ/ in an English as a foreign language (EFL) context. It attempts to identify the influence of this perception on the students' spoken word recognition and examine the correlation between perception and production of flapping on the one hand, and academic achievement on the other. It also seeks to provide solutions to help Arab students improve their perception of connected speech features. To achieve its objectives, the study carried out experimental tests and interviews. The results of the study show that the ability to produce the allophonic variant /ɾ/ in one's own speech has a positive correlation with its perception. In contrast, academic achievement does not significantly correlate with the perception of the allophone.